CII Education: An Offering Concept for Indonesian Education (Study on SMK KITA and EF-ILC) - Putro, Yusup Lintang Cahyo Andrian; Afriyanti, Rafika; Sandi, Fadri Ari; Parassa, Helni Sadid (Ilomata International Journal of Social Science, 2025)
Indonesia's goal to achieve the vision of “Indonesia Emas 2045” requires the role of the education sector. However, the current education system faces several critical challenges, such as corruption, discrimination, declining nationalism, and ineffective governance, which can hinder sustainable development. This research proposes the Contextualized Inclusive and Integrative Education (CII Education) model as an innovative framework to address these issues. The main objective of this research is to analyze and integrate three key educational concepts, namely Contextual Teaching and Learning (CTL), Inclusive Education, and Integration Education, into a comprehensive educational approach that aligns with national development goals. Using a qualitative research methodology, this study employs literature reviews, field observations, and empirical data collection from two institutions: SMK KITA and EF-ILC. CTL improves student engagement and critical thinking, while Inclusive Education ensures accessibility without discrimination. Moreover, TIE strengthens long-term knowledge retention by linking students’ cognitive, emotional, and social learning processes. Data findings from observed classrooms suggest that the CII model enhances students' academic performance and social adaptability. The study concludes that CII Education provides a structured and adaptable solution for improving Indonesia’s education system. Its implications in the future will include policy recommendations for national education reforms, teacher training programs, and industry-academic collaborations. Further research is required to explore the scalability of this model across different socio-economic and educational settings to ensure sustainable educational development in Indonesia.